STUDI LITERATUR: PENGARUH MEDIA DIGITAL PEMBELAJARAN TERHADAP HASIL BELAJAR MATEMATIKA - Lestari, Fajriah Dwi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The rapid development of digital technology has driven a significant transformation in the world of education, including in learning mathematics, which is often considered difficult and abstract by students. This article aims to examine the effect of using digital media on mathematics learning outcomes through a literature study approach. The method used is a literature study by reviewing fifteen scientific articles published in accredited journals at least SINTA 4. The analysis process is carried out descriptively qualitative by examining the effectiveness of various digital media, such as Geogebra, Desmos, LMS, interactive PowerPoint, and others on improving student learning outcomes, interest, and mathematical thinking skills. The results show that most digital media contribute positively to improving the quality of mathematics learning, both in terms of learning outcomes and student motivation. However, the effectiveness of the media is also influenced by external factors such as teacher readiness and infrastructure. The conclusion of this study emphasizes the importance of selecting the right media that is relevant to students' needs and the need for policy support and teacher training in the integration of technology into mathematics learning. This study also opens opportunities for the development of digital media based on student needs and further research on the integration of soft skills and personalization of learning styles in digital mathematics education. ABSTRAKPerkembangan teknologi digital yang pesat telah mendorong transformasi signifikan dalam dunia pendidikan, termasuk dalam pembelajaran matematika yang kerap dianggap sulit dan abstrak oleh siswa. Artikel ini bertujuan untuk mengkaji pengaruh penggunaan media digital terhadap hasil belajar matematika melalui pendekatan studi literatur. Metode yang digunakan adalah studi pustaka dengan menelaah lima belas artikel ilmiah yang dipublikasikan pada jurnal terakreditasi minimal SINTA 4. Proses analisis dilakukan secara deskriptif kualitatif dengan mengkaji efektivitas berbagai media digital, seperti Geogebra, Desmos, LMS, PowerPoint interaktif, dan lainnya terhadap peningkatan hasil belajar, minat, serta keterampilan berpikir matematis siswa. Hasil kajian menunjukkan bahwa sebagian besar media digital berkontribusi positif dalam meningkatkan kualitas pembelajaran matematika, baik dari sisi hasil belajar maupun motivasi siswa. Namun, efektivitas media juga dipengaruhi oleh faktor eksternal seperti kesiapan guru dan infrastruktur. Simpulan dari kajian ini menegaskan pentingnya pemilihan media yang tepat dan relevan dengan kebutuhan siswa serta perlunya dukungan kebijakan dan pelatihan guru dalam integrasi teknologi ke dalam pembelajaran matematika. Kajian ini juga membuka peluang untuk pengembangan media digital berbasis kebutuhan siswa dan penelitian lebih lanjut mengenai integrasi soft skills dan personalisasi gaya belajar dalam pendidikan matematika digital.